Nondiscounted Costs and Socially Discounted Benefits as Predictors of Cooperation in Prisoner's Dilemma Games. - Toledo, Aldo C.; Avila, Raul (Psychological Record, 2021)
Cooperation is commonly defined as an individual's choice that benefits both themself and others, in contrast to selfishness, which benefits the individual only. Cooperative behavior is more likely to occur when the benefit to others, discounted as a function of social distance (i.e., social discounting), is higher than the nondiscounted cost of cooperation Rachlin, H. & Locey, M. L. (Behavioural Processes 87, 25-33, 2011). We tested five 2-player prisoner's dilemma reward matrices with 117 participants, among which both nondiscounted cost and socially discounted benefit varied systematically. Costs and benefits were defined, respectively, as the amount the participant lost and the amount the other player won when the participant cooperated. In global terms, systematically increasing costs and decreasing benefits of cooperation decreased the percentage of participants who cooperated, as predicted. These results suggest that the balance of costs and benefits of cooperation is useful for predicting cooperative behavior in social situations, such as prisoner's dilemma games.